Hierarchical porous carbon derived from coal and biomass for high performance supercapacitors. (1st March 2022) - Zhang, Xiaoyun; Sun, Bingkang; Fan, Xing; Liang, Peng; Zhao, Guoming; Saikia, Binoy K.; Wei, Xianyong
Graphical abstract: Highlights: Mass spectrometry was used to underatand the molecular composition of carbon precursors. Reveal the relationships between composition of precursor and performance of supercapacitors. N- and O-containing compounds can improve the conductive and capacitance of carbon materials. Abstract: In this work, soluble portions obtained from the co-thermal dissolution (CTD) of rice husk (RH) and coal were used as the carbon precursor for the synthesis of 3D hierarchical porous carbons (HPCs). The electrochemical properties of HPCs were tested in supercapacitors as working electrode. HPC-RH3/1 showed a specific capacitance of 352 F/g at 1 A/g and a retention rate of 100% after 10, 000 cycles. The composition of the carbon precursors is a key factor determining the characteristics of carbon-based materials. The detailed composition of carbon precursors was obtained by gas chromatography/mass spectrometry (GC/MS) and Orbitrap MS. The N-containing organic matters in carbon precursors can improve conductivity and the O-containing compounds can contribute to pseudocapacitance. According to the MS analysis, the high content of compounds with unsaturated structures was of benefit to excellent electrochemical properties. The study on the relationships between molecular compositions of carbon precursors and electrochemical characteristics can give a direction of selection and optimization of carbon precursors, which further improve the electrochemical performance of carbon materials.